Pengaruh Kualitas Produk dan Brand Image terhadap Kepuasan Konsumen Sepatu Basket Nike di Kota Malang - Endyarta Abdul Aziiz Al Fatah; Rizky Kurniawan Murtiyanto; Ayu Sulasari (STIKes Ibnu Sina Ajibarang, 2025)
Globalization and increasing competition cause companies to compete with each other to get the attention of consumers, so that companies are required to be innovative and creative in responding to various changes in the dynamic environment. The main objectives of this study are to determine and analyze the significant influence between Product Quality and Brand Image on Customer Satisfaction on Nike Basketball Shoes. This research was a quantitive research using IBM SPSS Statistics 25 for analytics. The sampling technique used was using accidental sampling techniques. Online questionnaires were distributed to 100 respondents in a population of Malang City who were a student, self employed and coach as main job. The results of this study indicate that the higher the Product Quality and Brand Image, the higher the Customer Satisfaction. Each variable partially affects Customer Satisfaction and shows that Product Quality and Brand Image variables affects Customer Satisfaction. It also shows that Product Quality and Brand Image simultaneously have a positive effect on Customer Satisfaction. Based on the results of the study, it can be concluded that the Product Quality and Brand Image variables have effects on Customer Satisfaction.